BBr3‐Mediated P(III)‐Directed C−H Borylation of Phosphines. Issue 9 (27th December 2021) - Lv, Jiahang; Zhang, Xue‐Jun; Wang, Minyan; Zhao, Yue; Shi, Zhuangzhi
Abstract: Transition‐metal‐catalyzed C−H borylation has been widely used in the preparation of organoboron compounds. Here, we developed a general protocol on metal‐free P(III)‐directed C−H borylation of phosphines mediated by BBr3, resulting in the formation of products bearing both phosphorus and boron. The development of the metal‐free strategy to mimic previous metallic processes has shown low cost, superior practicality, and environmental friendliness. Density functional theory (DFT) calculations demonstrate the preferred pathway for this metal‐free directed C−H borylation process. Abstract : Boron Chemistry . An efficient metal‐free system has been uncovered for the site‐selective C−H borylation of phosphines directed by P(III) atom just using BBr3 . This robust method enables the rapid construction of phosphine boronate esters in selective, practical, low‐cost, and environmentally friendly modes.